2013
DOI: 10.1111/ctr.12199
|View full text |Cite
|
Sign up to set email alerts
|

Alemtuzumab induction in simultaneous pancreas and kidney transplantation

Abstract: There are no differences in patient, pancreas or renal allograft survival using AZ induction. AZ may confer an advantage in the perioperative period as evidenced by a decreased hospital length of stay. However, this benefit may be lost due to more frequent rehospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
(61 reference statements)
0
6
1
Order By: Relevance
“…It has long been debated whether lymphocyte‐depleting induction confers favorable results in pancreas transplantation. In contrast to previous studies , this report suggests that there is a significant graft survival benefit in using lymphocyte‐depleting agents at induction (Fig. ), without compromise in patient survival (p = 0.535).…”
Section: Discussioncontrasting
confidence: 99%
“…It has long been debated whether lymphocyte‐depleting induction confers favorable results in pancreas transplantation. In contrast to previous studies , this report suggests that there is a significant graft survival benefit in using lymphocyte‐depleting agents at induction (Fig. ), without compromise in patient survival (p = 0.535).…”
Section: Discussioncontrasting
confidence: 99%
“…In kidney transplant alone (KTA), the induction with ATG followed by steroid-free maintenance IS, achieved a graft survival rate similar to that of historical KTA recipients who received the triple maintenance IS with fewer CMV infections, posttransplant diabetes cataract, and avascular necrosis when compared to historical controls with the same induction IS but receiving the triple maintenance IS [ 20 , 21 ]. Similarly, steroid-free maintenance IS, following induction with alemtuzumab, was associated with favorable graft and adverse events outcomes in KTA [ 8 , 9 , 11 , 12 , 14 ] and SPK recipients [ 12 , 15 , 22 26 ] compared to induction with ATG or nonlymphocytes depleting agents, with either triple or prednisone-free maintenance IS. In these studies, the total alemtuzumab doses were 40–60 mg given in 20–30 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…These findings contradict others by Pascual et al who found that among SPK recipients, an induction with two doses of alemtuzumab was associated with a lower rate of ACR (3%) when compared to basiliximab (15%), P =0.02 but was not protective against AMR with a rate of 18% vs. 14%, P =0.6 [ 27 ]. Most of the other studies evaluating the effectiveness of steroid-free maintenance IS following induction with alemtuzumab did not differentiate AMR and ACR, and found similar [ 15 , 23 26 , 28 ] or better [ 22 ] rejection and graft survival rates when compared to the conventional IS. When our group reported their 6-month experience with the EAE and CNI- and steroid-free maintenance IS, we noted higher rates of graft loss due to rejection in PTA (15% vs. 3%, P =0.06) and a higher rate of first reversible rejection in SPK (41% vs. 9%, P =0.0003), compared to PTA and SPK in a historical SIM group, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some B-cell depleting therapies have been reported but used very infrequently (<0.6%), and were not be the focus of this review. All three induction therapies have acceptable rates of rejection, with multiple observational and prospective studies finding very little difference between the three [143][144][145][146][147][148][149][150][151][152][153][154][155][156].…”
Section: Immunosuppressionmentioning
confidence: 99%